Reformulation of The Administrative Examination Regulation of Applications for Review (Peninjauan Kembali) in Criminal Cases: A Comparative Study of Indonesia, The Netherlands and France - Dipa Rivaldi; Muktiono (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The regulation of the administrative examination of applications for extraordinary legal remedy of review (peninjauan kembali, PK) in Indonesian criminal procedure contains fundamental juridical problems. Although PK is regulated in Articles 263–269 of the Criminal Procedure Code (KUHAP 1981) as amended by KUHAP 2025, significant procedural ambiguity persists, particularly at the examination stage before the district court functioning as the forwarding court. This research aims to analyze the juridical problems in the regulation of PK under KUHAP regarding the procedure for examining PK applications, to compare the administrative examination regulation between Indonesia, the Netherlands, and France, and to formulate a reformulation model adoptable from those jurisdictions. This study employs a normative legal method with a prescriptive and applied character, utilizing the statute approach, conceptual approach, and comparative approach. Legal materials consist of primary, secondary, and non-legal materials analyzed prescriptively. The findings reveal that the procedural obscurity of Article 265 KUHAP, the ambiguity of the concept of novum, and the disharmony between statutory provisions and internal Supreme Court regulations generate legal uncertainty and disparities in application. The Dutch Wetboek van Strafvordering (Articles 457–482i) and the French Code de procédure pénale (Articles 622–627) provide more structured, transparent, and accountable mechanisms. This article proposes a reformulation model encompassing clarification of novum criteria, detailed examination procedures, adoption of best practices from both countries, and harmonization of the regulatory hierarchy.